2018
DOI: 10.3389/fimmu.2018.02354
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Peripheral Blood Leukocytosis Is Negatively Correlated With T-Cell Infiltration Predicting Worse Outcome in Colorectal Cancers

Abstract: We aimed to explore the prognostic value of blood leukocyte and to generate a predictive model to refine risk stratification for colorectal cancers. 6,558 patients with colorectal cancers were identified eligible respectively in Fudan University Shanghai Cancer Center (FUSCC) between May, 2008 and October, 2016. Then the entire set is divided into a training set and a testing set. The prognostic value of pretreatment white blood cell count and clinicopathologic parameters in the context of tumor-infiltrating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
(29 reference statements)
2
17
0
Order By: Relevance
“…At present, several immune risk score models used to quantify the immune status and indicate the prognosis of patients have been proposed in colorectal cancer and breast cancer respectively. These immune risk score models was proposed based on the counts of two lymphocyte populations of tumor centers and invasion margins [ 45 , 46 ]. The immune risk score model can be used to identify patients with recurrent risk or benefit from corresponding adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, several immune risk score models used to quantify the immune status and indicate the prognosis of patients have been proposed in colorectal cancer and breast cancer respectively. These immune risk score models was proposed based on the counts of two lymphocyte populations of tumor centers and invasion margins [ 45 , 46 ]. The immune risk score model can be used to identify patients with recurrent risk or benefit from corresponding adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that peripheral blood leukocytosis and neutrophilia re ected cancerrelated in ammation and has been proposed as prognostic immunological biomarkers for various malignancies 11,21 . A study validated leukocytosis as an independent prognostic factor in CRC, which provided for the rst-time vital insight on the correlation of peripheral pretreatment leukocytosis with the tumor-in ltrating cells contexture and might be relevant for future risk strati cation 22 . A meta-analysis showed that preoperative leukocytosis was common and correlates with poor pathological and survival outcomes in endometrial carcinoma patients 23 .…”
Section: Discussionmentioning
confidence: 99%
“…CRC is an inflammation-related tumor characterized by the infiltration of heterogeneous immune cells into tumor microenvironment and peripheral hematological disorders (6), which create a complex microenvironment that allows for the development of tumors (7 ). During acute inflammation, white blood cells (WBCs) are considered the first line of defense against microbial infection, protecting the host from pathogens (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the state of long-term activation, continuous production of growth factors and reactive oxygen species may lead to permanent genomic changes and hinder the recruitment of lymphocytes by interacting with the DNA of the proliferating epithelium. Moreover, leukocytosis inhibits the activation of CD8 + tumor infiltrating lymphocytes by upregulating programmed death protein 1 (PD-1) on T lymphocytes and myeloid cells (7,9). In malignant diseases, leukocytes and neutrophils can dilate locally and throughout the body, promoting anti-cancer treatment resistance and tumor progression through angiogenesis, invasion, and inhibitory factors (10).…”
Section: Introductionmentioning
confidence: 99%